Hepatitis B infection awareness, vaccine perceptions and uptake, and serological profile of a group of health care workers in Yaoundé, Cameroon - Henri Olivier Pambou Tatsilong; Jean Jacques N. Noubiap; Jobert Richie N. Nansseu; Leopold N. Aminde; Jean Joel R. Bigna; Valentine Ngum Ndze; Roger Somo Moyou (BMC, 2016)
Abstract Background Cameroon is one of the countries in Africa with the highest burden of Hepatitis B infection. Health care workers are known to be at risk of occupational exposure to blood and other infectious bodily fluids. The aim of this study was to assess the profile of serological markers of hepatitis B virus (HBV) infection, knowledge and perceptions regarding HBV infection among health care workers in a health area in Yaoundé. Methods A cross-sectional study was conducted in the Mvog-Ada Health Area of the Djoungolo Health District from March 1 to November 31, 2014. All consenting health care workers were included in the study. Serological markers of HBV (HBs Ag, Hbe Ag, anti-HBs Ab, anti-HBe Ab, anti-HBc Ab) were qualitatively tested using Biotech®(OneHBV-5 parameter rapid test website) in each participant and the anti-HBs antibodies were quantified by ELISA (Biorex) among those who were positive with the qualitative test. Chi square test or its equivalents were used to compare qualitative variables and a p-value less than or equal to 0.05 was considered significant. Result A total of 100 participants were retained for the study out of 163 in the health area giving a response rate of 61.34 %; the mean age was 30.5 (SD 6.8) years and 71 % of participants were women. Forty seven percent (47 %) of workers had good level of knowledge of HBV infection. The men were 3.20 times (95 % CI: 1.02-9.19, p = 0.04) more likely to have a good level of knowledge than women. Participants with a university study level were more (95 % CI: 3.17-25, p < 0.0001) likely to have a good level of knowledge than those with a high school study level. Ninety-six percent of participants thought that they were at a greater risk of becoming infected with HBV than the general population, 93 % felt that the vaccine should be compulsory and all (100 %) were willing to recommend it to others. However, only 19 % had received at least one dose of the vaccine. The proportion of HBs Ag was 11 %. The different serological profiles with regard to HBV infection were naive subjects (62 %), chronic carriers (11 %), vaccinated (19 %) and subjects naturally immunized (8 %). Three out of the 19 participants who received at least one dose of the vaccine, only 9 (47.4 %) of whom had titers ≥100 IU/l indicating a good response to vaccination. Among those who received three doses of the vaccine (n = 12, 63 %), 2 (16, 66 %) had poor response to vaccination (HBs Ab titers < 100 IU/l). Conclusion The prevalence of HBs Ag among health care workers in the Mvog-Ada Health Area is high (11 %). These workers are at high risk of HBV infection because of very low vaccine uptake and poor post-exposure practices. Their knowledge of HBV infection is non-optimal.